Silver Nanoparticles in PEDOT:PSS Layer for Polymer Solar Cell Application - Agnieszka Iwan; Bartosz Boharewicz; Igor Tazbir; Andrzej Sikora; Beata Zboromirska-Wnukiewicz (International Journal of Photoenergy)
We compare the performance of polymer solar cells based on poly(3-hexylthiophene) (P3HT) and [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) with silver nanoparticles (Ag NPs) incorporated in poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS). The structure of constructed solar devices was ITO/PEDOT:PSS:Ag NPs/P3HT:PCBM/Al. Typical polyol chemistry was used to synthesize silver in water solution. Ag nanoparticles were investigated by UV-vis, atomic force microscopy (AFM), and dynamic light scattering (DLS) methods. We investigated influence of amount of silver in a hole transporting layer on the performance of bulk heterojunction polymer solar cells. The value of power conversion efficiency (PCE), equal to 2.16% under simulated 100 mW/cm2 AM 1.5G irradiation, was found for device created in air with 60 µL of Ag NPs added to 1 mL of PEDOT:PSS. Along with the increase amount of Ag NPs from 60 to 150 µL, the PCE decrease was found. Stability of solar cells with Ag was also investigated. The loss in value of PCE after 8 months was found in the range 13–47% depending on the device architecture. The solar cells were additionally measured with impedance spectroscopy.